Beam-type experimental study on interfacial bond-slip behavior of steel reinforcement recycled concrete. (10th October 2022) - Ma, Jinfeng; Bai, Guoliang; Ma, Haozhao; Bai, Xueyi; Ni, Tao
Highlights: Beam test were used to investigate the bond behavior between steel and recycled concrete. Influence of recycled aggregate replacement ratio on bond behavior. The calculation formulas of the interfacial bond strength of SRRC. The constitutive relations of the bond-slip. Abstract: Four steel reinforcement recycled concrete (SRRC) specimens were designed and tested to investigate the bond behavior at the interface between steel and recycled concrete. The parameters of test is the replacement ratio of recycled coarse aggregate. The results show that bond-slip failure occurred in all the specimens (except SRRC-B01), and the ultimate bearing capacity of the specimens increased at first and then decreased with the increase of the replacement ratio of recycled coarse aggregate. When the replacement ratio is 70%, the ultimate bearing capacity is largest, which is about 19.2% higher than that replacement ratio is 0, and about 7% higher than that replacement ratio is 100%. The interfacial bond strength of steel and recycled concrete increase at first and then decreased with the increase of replacement ratio, and the law of slip at loading end is similar to bond strength, they all reach the maximum value when the replacement ratio is 70%. According to the analysis of the test results, the calculation formulas of bond strength and slip at loading end with the consideration of replacement ratio of recycled coarse aggregate were proposed, and the accuracy of the formulas is verified by comparing with the test data. Finally, the bond-slip constitutive relation at the interface between steel and recycled concrete was established, and a segmented representation model was proposed. The fitted values are in good agreement with the test values. The investigation of this paper can provide reference for relevant scientific research and engineering design.